Developing web-based partner relationship management: An exploratory study of the application of web-based solutions by ICT companies in Malaysia, Ireland and the United Kingdom - Kedah, Zulkarnain; Jan, Muhammad Tahir; Haque, A. K. M. Ahasanul; Ahmed, Farruk (2016)
Web technologies have a significant impact on how companies manage their relationships with their stakeholders. Technologies, especially web portals have been widely adopted as platforms for integrating partner or reseller activities. Inefficient traditional methods which require high transaction costs and poor communication processes are being replaced with web-based relationship management solutions. This study explores the adoption of webbased technologies, specifically web portals in partner relationship management (PRM) and their contributions towards enhancing and sustaining relationships with channel members. This study is based on prior research and interview data gathered from a sample of ten companies in the Information Communication Technology (ICT) industry from Malaysia, Ireland and the United Kingdom. The findings revealed that companies which adopt web-based solutions become effective and efficient in three main areas: sales and marketing, training, and technical support to their partners. Overall, web-based PRM adds more value to the business processes of these countries.